Use of Molecular Biology for Identifying Benign Hepatocellular Tumors Leads to More Personalized Medicine - Vinall, Maria (MD Conference Express, 2014)
Benign hepatocellular adenomas are not a uniform liver disease but include different types of tumors, which can be classified as hemangioma (nonepithelial), focal nodular hyperplasia, and hepatocellular adenoma, the latter 2 being epithelial tumors. This article discusses how insights from molecular biology have profoundly changed our clinical understanding of benign liver tumors and how using the genotype-phenotype classification of these tumors can identify new etiologies, as well as diagnostic and prognostic features of this disease.